Bicyclo[1.1.1]pentane Embedded in Porphyrinoids** - Senge, Mathias (My University, 2023)
We report a two-step approach to obtain synthetically versatile bicyclo[1.1.1]pentane (BCP) derivatives using Grignard reagents. This method allows the incorporation of BCP units in tetrapyrrolic macrocycles and the synthesis of a new class of calix[4]pyrrole analogues by replacing two bridging methylene groups with two BCP units. In addition, a doubly N-confused system was also formed in the presence of electron-withdrawing substituents at the BCP bridgeheads. The pyrrole rings in BCP containing macrocycles exist in 1,3-alternate or αβαβ conformations, as observed from single-crystal X-ray diffraction analyses and 2D NMRspectroscopy.